1982
DOI: 10.1161/01.res.50.6.848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine on the energy metabolism of K+-depolarized hog carotid artery.

Abstract: In a previous study (Peterson and Glück, 1982), activation of hog carotid artery with high-K+ medium caused no increase in aerobic glycolysis (lactic acid production). In contrast, histamine alone is found to stimulate aerobic glycolysis in a tension-dependent fashion (GLück and Paul, 1977). In this study, the addition of histamine to the already K+-depolarized hog carotid artery induced additional contraction, elevated tissue cyclic adenosine 3',5'-monophosphate [cAMP] levels, coupled the rate of aerobic glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Activation by K + for Na + substitution in hog carotid artery stimulates only a small and not significant increase in tissue cAMP (Peterson 1982), whereas no effect on cAMP has been reported for K + depolarization of rabbit aorta (van Breeman, 1976). Thus, it is reasonable to expect, under these conditions, that the same level of steady isometric tension reflects similar cytoplasmic freeCa ++ levels.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Activation by K + for Na + substitution in hog carotid artery stimulates only a small and not significant increase in tissue cAMP (Peterson 1982), whereas no effect on cAMP has been reported for K + depolarization of rabbit aorta (van Breeman, 1976). Thus, it is reasonable to expect, under these conditions, that the same level of steady isometric tension reflects similar cytoplasmic freeCa ++ levels.…”
Section: Discussionmentioning
confidence: 88%
“…Experiments were performed at the muscle length optimal for isometric tension generation and at 37°C. (Ore Res 50: 839-847, 1982) \N THIS and a subsequent report (Peterson 1982), we compare the metabolic energy cost of isometric tension maintenance in the isolated hog carotid artery under three sets of activating conditions by which the level of isometric tension development may be altered in a stable graded fashion. In all three conditions, activation with high extracellular K + is used.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, the magnitude of this contraction-independent energy utilization is not as great as that induced by bethanechol (Levin et al , 1991bRuggieri et al 1988). Similar observations have been made in vascular smooth muscle; histamine stimulated glycolysis to a significantly greater extent than did KCl (Peterson, 1982). …”
Section: -Ementioning
confidence: 73%
“…Muscarinic stimulation of cell-surface receptors activates a membrane-bound G-protein signaling pathway to the intracellular contractile apparatus, whereas KCl stimulation depolarizes the cell membrane, initiating contraction more directly [5,16]. Similar to these observations of bladder smooth muscle metabolism, Peterson [17] observed that histamine stimulates vascular smooth muscle glycolysis to a greater degree than KCl.…”
Section: Introductionmentioning
confidence: 76%